A importância do letramento literário para alunos do 9º ano do ensino fundamental nas escolas: Santa Terezinha em Abaetetuba e Ayrton Senna de Silva em Muaná - BENTES, Daiany Costa (2023)
Based on the idea that literature is frequently present in the life do each individual, this monograph aims to investigate the process of literary literacy, highlighting literature the teaching, as well as to enable reading strategies for students in the 9th grad in two basic education schools, in different municipalities. The aim of the research is to promote literary literacy texts, with a view to contributing to the students’ personal development regarding literature, making them readers and actors in the social environment in which they live. The national curricular parameters (PCNs) and theories of Cosson (2016), Soares (2004), Candido (2000), Bosi (2006), among others, address and approach concepts and improvements regarding reading, literacy and literature. To complete the ideas, a qualitative research was carried out to verify the students, through an intervention sequence. In the face of this, the results revealed that literary literacy in elementary education has not yet fully materialized due to the distinct realities between the selected schools for the application, but the importance of literary teaching is still believed. Finally, it is concludes that this type of study, despite the controversies of life, can contribute significantly to the relationship literature and society, making readers critical and expressive readers able to observe the word as it actually presents itself.